WSX-1 signalling inhibits CD4⁺ T cell migration to the liver during malaria infection by repressing chemokine-independent pathways. - Ana Villegas-Mendez; Emily Gwyer Findlay; J Brian de Souza; Lisa-Marie Grady; Christiaan J Saris; Thomas E Lane; Eleanor M Riley; Kevin N Couper (PLoS ONE)
IL-27 is an important and non-redundant regulator of effector T cell accumulation in non-lymphoid tissues during infection. Using malaria as a model systemic pro-inflammatory infection, we demonstrate that the aberrant accumulation of CD4⁺ T cells in the liver of infected IL27R(-/-) (WSX-1(-/-)) mice is a result of differences in cellular recruitment, rather than changes in T cell proliferation or cell death. We show that IL-27 both inhibits the migratory capacity of infection-derived CD4⁺ T cells towards infection-derived liver cells, but also suppresses the production of soluble liver-derived mediator(s) that direct CD4⁺ T cell movement towards the inflamed tissue. Although CCL4 and CCL5 expression was higher in livers of infected WSX-1(-/-) mice than infected WT mice, and hepatic CD4⁺ T cells from WSX-1(-/-) mice expressed higher levels of CCR5 than cells from WT mice, migration of CD4⁺ T cells to the liver of WSX-1(-/-) mice during infection was not controlled by chemokine (R) signalling. However, anti-IL-12p40 treatment reduced migration of CD4⁺ T cells towards infection-derived liver cells, primarily by abrogating the hepatotropic migratory capacity of T cells, rather than diminishing soluble tissue-derived migratory signals. These results indicate that IL-27R signalling restricts CD4⁺ T cell accumulation within the liver during infection primarily by suppressing T cell chemotaxis, which may be linked to its capacity to repress Th1 differentiation, as well as by inhibiting the production of soluble, tissue-derived chemotaxins.